2016
DOI: 10.1007/s13277-016-5318-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression and significance of Hippo/YAP signaling in glioma progression

Abstract: Dysregulation of Hippo/YAP signaling leads to aberrant cell growth and neoplasia. Although the roles and regulation of Hippo/YAP signaling were extensively studied in cancer biology recently, study systematically checking the expression pattern of core components of this pathway at the tumor tissue level remains lacking. In this study, we thoroughly examined the profile of core components of Hippo/YAP signaling in patient specimens both at the mRNA and at protein levels. We found that the mRNA level of YAP1/TA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 42 publications
3
50
0
Order By: Relevance
“…For example, it acts as an oncogene in liver, 23 pancreas 24 cancers, whereas it exerts as a tumor suppressor in some breast cancers. 25 In glioma, YAP1 and their target genes, CRY61, CTGF, and BIRC5 were identified to be significantly amplified in glioma tissues, and upregulation of YPA1 enhanced cell proliferation ability and conferred glioma cells cisplatin-resistance, [26][27][28] illustrating that YAP1 plays a role in glioma chemosensitivity. Moreover, Zhang et al 29 reported that inhibition of TAZ, an effector of Hippo signaling significantly promoted radiation-induced senescence and growth inhibition in glioma cells, suggesting a vital role of Hippo signaling plays in glioma radiosensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it acts as an oncogene in liver, 23 pancreas 24 cancers, whereas it exerts as a tumor suppressor in some breast cancers. 25 In glioma, YAP1 and their target genes, CRY61, CTGF, and BIRC5 were identified to be significantly amplified in glioma tissues, and upregulation of YPA1 enhanced cell proliferation ability and conferred glioma cells cisplatin-resistance, [26][27][28] illustrating that YAP1 plays a role in glioma chemosensitivity. Moreover, Zhang et al 29 reported that inhibition of TAZ, an effector of Hippo signaling significantly promoted radiation-induced senescence and growth inhibition in glioma cells, suggesting a vital role of Hippo signaling plays in glioma radiosensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…While it is now well established that YAP1 is strongly involved in tumorigenesis, notably by regulating cell proliferation, its role in gliomas remains poorly investigated . Currently, several studies have demonstrated the implication of YAP1 in glioma cell proliferation using shRNA or overexpression‐based approaches . However, these studies were performed on conventional glioma cell lines (U87 and U251) that had been isolated long before use and no longer accurately reflected the initial pathology .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, they observed that overexpression of LATS1 downregulated the YAP1 protein level, inhibited cell proliferation, induced cell apoptosis and cell cycle arrest in 786-O cells (39). LATS1 downregulation and its contribution to cancer progression has been observed in other malignances such as glioma (40), nosopharyngeal carcinoma (41), astrocytoma (42), non-small cell lung cancer (18), breast cancer (16), colorectal cancer (17) and renal carcinoma (39). Additionally, association between LATS1 hypermethylation and tumor progression has been noted in lung cancer (43), schwannomas (44), oral squamous cell carcinoma (45), colorectal cancer (17) and astrocytoma (42), however, the authors did not observe the influence of LATS1 methylation status on patient outcome.…”
Section: ------------------------------------------------------------mentioning
confidence: 96%